(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
This research is driven by modern food industry trends toward developing products with improved nutrient profiles and the rational utilization of secondary raw materials. Traditional meat pâté formulations are often high in fat, while the significant potential of collagen-rich materials, particularly pork skin, remains underutilized. A promising approach involves their use as protein-fat emulsions (PFEs) stabilized by alternative flours (oat, buckwheat, and pumpkin). This method aligns with circular economy principles and enriches the final product with functional ingredients. The objective was to scientifically validate and develop a technology for liver pâté, partially replacing fat with these PFEs, and to evaluate their quality characteristics. A control and three experimental samples were prepared. The experimental samples incorporated 15% emulsion (50% pork skin, 15% oil, 25% water, and 10% of the respective flour), replacing a portion of the raw fat and water. Samples were assessed using standard organoleptic, physicochemical (moisture, protein, fat, and ash content), and microbiological methods. The addition of PFEs did not impair organoleptic properties (taste, aroma, texture). Furthermore, protein and fat contents in the experimental samples showed no significant difference from the control. A significant moisture reduction (from 66.4 g to 62.2–63.2 g) was observed, indicating the high water-binding capacity of the plant-based stabilizers. The most substantial advantage was the product’s mineral enrichment: the ash content in the test samples (2.65–2.85 g) was nearly double that of the control (1.45 g). All samples met microbiological safety requirements. Consequently, the study confirms the technological feasibility of using these developed PFEs, demonstrating a rational use of collagen-rich raw material and enhancing the nutritional value of pâté while maintaining high consumer appeal.